Female Pakistani carers' views on future formal and informal care for their older relatives in Norway - Sanjana Arora; Bernd Rechel; Astrid Bergland; Melanie Straiton; Jonas Debesay (BMC, 2020)
Abstract Background The aging of Pakistani immigrants in Norway raises questions related to their increased need for care and help from relatives, as well as those concerning what future formal and informal care and healthcare accessibility for older immigrants may look like. The hidden nature of family caregiving means that the circumstances of carers, their views and their dilemmas related to future care are largely invisible. In this study, we explored female Pakistani carers' views of future care and healthcare accessibility for their older relatives in Norway. Methods Our data included interviews with family carers between the ages of 23 and 40 years old, living in Oslo, Norway. We recruited ten family carers, out of which eight were daughters and two were daughters-in-law. Interviews were conducted by the first author in Urdu or English and were recorded and transcribed verbatim. Results Our findings revealed several factors that influenced participants' perceptions about formal and informal caregiving, which can be organised into the following themes: 1) caring for family in Norway as in Pakistan, 2) worries about being 'dropped off' at a care home, 3) concerns about being cared for by outsiders, 4) questions about what other people might say and 5) adhering to society's expectations of a 'good' carer. Conclusion Family carers' traditional views of filial piety do not entirely determine the use of or access to healthcare services of their older relatives. There is a need to develop culturally sensitive healthcare systems so that immigrant families and their carers have more options in choosing care in old age, which in turn will ease their families' care burden. Healthcare professionals and policymakers should not assume that immigrant families will take care of their own older members but should instead secure adequate support for older immigrants and their family carers.